Black tea and maintenance of normal endothelium‐dependent vasodilation: evaluation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006. (16th January 2018) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdor, Inge; McArdle, Harry J; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Following an application from Unilever NV, submitted for authorisation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 via the Competent Authority of Ireland, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to black tea and maintenance of normal endothelium‐dependent vasodilation. The scope of the application was proposed to fall under a health claim based on newly developed scientific evidence. The food proposed by the applicant as the subject of the health claim is black tea beverages, either freshly prepared or reconstituted from water extract powders of black tea, characterised by the content of flavanols (expressed as catechins plus theaflavins) of at least 30 mg per 200 mL serving. The Panel considers that black tea characterised by the content of flavanols (expressed as catechins plus theaflavins) is sufficiently characterised. The claimed effect proposed by the applicant is 'improvement of endothelium‐dependent vasodilation'. The Panel considers that maintenance of normal endothelium‐dependent vasodilation is a beneficial physiological effect. Of the five human intervention studies provided on the chronic effect of black tea consumption on endothelium‐dependent vasodilation, two investigated the effect after regular consumption of black tea for a sufficiently long time period (i.e. at least 4 weeks). These two studies did not allow an effect of black tea on endothelium‐dependent vasodilation to be established. The Panel concludes that a cause and effect relationship has not been established between the consumption of black tea and maintenance of normal endothelium‐dependent vasodilation.